ANALISIS PENERIMAAN DAN PEMAHAMAN MASYARAKAT TERHADAP INFORMASI IZIN MENDIRIKAN BANGUNAN DI KABUPATEN MAROS - Sudirman Sudirman; Muhammad Farid (KAREBA : Jurnal Ilmu Komunikasi, 2016)
This study aimed to (1) information conveyed to the public regarding building permits, (2) channel information that is used to convey information building permits, (3) acceptance and understanding of the information society building permits. This study was conducted in Maros. This type of research is survey method with mixed methods approach which is a combination of qualitative methods and quantitative methods. Sampling was done by using simple random sampling of the population who are users of building permits during the year 2013-2014, while informants selected intentionally by certain considerations. Data were collected through questionnaires, interviews, observation and documentation were then analyzed using quantitative descriptive technique. Research results show that: (1) the information submitted regarding the building permits include the prohibition to build without building permits, benefits and purpose building permits, conditions that must be met for the issuance of building permits, maintenance procedures, the time period, the fees as well as sanctions against people who violate building permit, (2) information channels used are billboards, radio, website, brochure, socialization and care workers, (3) acceptance and understanding of the information society of building permits showed a fairly good category in meaning people have to know and understand well enough the importance of building permits before starting the building activity.